Research Progress on Role of Probiotic Akkermansia Muciniphila in Oncogenesis, Development and Treatment of Tumor - ZHAO Honghui; WANG Yudong (Zhongliu Fangzhi Yanjiu, 2023)
Although tumor treatment models have been continuously improved in clinical practice, cancer remains a serious threat to human health. The effect of probiotics on tumor therapy has received extensive attention. As a common colonizer of the intestinal mucosa, Akkermansia muciniphila(AKK) has a well-defined role in metabolic diseases, but its complex role in tumor development and therapeutic efficacy has not been fully elucidated. The unique properties and physiological roles of AKK play an important role in different solid tumors and it may be a potential biomarker. This article provides a review of previous studies and proposes clinical strategies to influence the abundance of AKK to provide a theoretical reference for the development of next-generation probiotics and the reshaping of the tumor treatment landscape.